A comparative study of post-operative outcomes in type 1 tympanoplasty using tragal chondroperichondrial shield graft and temporalis fascia graft - Muniasamy, Pradeep Kumar; Srinivasan, Dharanya Gopalakrishnan; Velayutham, Prabu; Savery, Nishanth; Krishnaswami, Balasubramanian; Vellikannu, Ramkumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Type 1 tympanoplasty is the reconstruction of perforated tympanic membrane with an intact and mobile ossicular chain. Among various autologous graft materials, temporalis fascia and tragal chondroperichondrium are commonly used, having their own merits and demerits. In our study, we have compared the results and postoperative outcomes of tympanoplasty using temporalis fascia and tragal chondroperichondrium. Methods: This prospective comparative study included 60 cases of chronic suppurative otitis media - tubotympanic disease (CSOM-TTD) in a tertiary care centre. They were randomised into two groups of 30 patients each and were subjected to tympanoplasty using either tragal cartilage-perichondrium (group 1) or temporalis fascia graft (group 2) from November 2017 to May 2019. Objective hearing improvement at 1st, 3rd and 6th month postoperative follow-up and graft uptake rate at 3rd month were compared. Results: Incidence of cases was more in the age group between 31-45 years age group (53.3%). Graft uptake rate was 96.6% for temporalis fascia group and 83.33% for tragal group (p value - 0.194). Preoperative air-bone (AB) gap in group 1 was found to be 25±4.09 dB which improved to 11.73±2.21 dB at 6 months and in group 2, it was 25.7±3.94 dB which improved to 14.06±3.68 dB at 6 months. Mean improvement in hearing for tragal group (13.27 dB) was better than temporalis fascia group (11.64 dB) (p value <0.001). Conclusions: Both temporalis fascia and tragal chondroperichondrium are suitable graft materials for tympanoplasty, although graft uptake was clinically better with the use of temporalis fascia.